The EnvZ-OmpR Two-Component Signaling System Is Inactivated in a Mutant Devoid of Osmoregulated Periplasmic Glucans in Dickeya dadantii - Caby, Marine; Bontemps-Gallo, Sébastien; Gruau, Peggy; Delrue, Brigitte; Madec, Edwige; Lacroix, Jean-Marie (Frontiers in Microbiology, 2018)
Osmoregulated periplasmic glucans (OPGs) are general constituents of alpha-, beta- and gamma-Proteobacteria. This polymer of glucose is required for full virulence of many pathogens including Dickeya dadantii. The phytopathogen enterobacterium D. dadantii causes soft-rot disease on a wide range of plant. An OPG defective mutant is impaired in environment sensing. We demonstrated previously that i) fluctuation of OPG concentration controlled the activation level of the RcsCDB system, ii) RcsCDB controlled with EnvZ/OmpR the OPG succinylation mechanism. These previous data lead us to explore whether the OPGs are required for other two-component system. In this study, we demonstrated that inactivation of the EnvZ/OmpR system in an OPG-defective mutant restored full synthesis of pectinase but only partially virulence. Unlike for RcsCDB system, the EnvZ-OmpR system is not controlled by the OPG concentration but required OPGs for proper activation.